Interdigital structures of heavy ions linear accelerators: their tuning, beams focusing and use (review) - Dyachenko, О.F. (Вопросы атомной науки и техники, 2019)
The review interdigital H-accelerating structures (IHAS) of the heavy ions linear accelerators developed in NSC KIPT throughout several tens of years is presented. It is shown that in structures with individual stems all kinds of focusings are applicable: quadrupole, grid, alternating-phase (APF, in various variants), high-frequency (in various variants) and their combinations. Corresponding constructive decisions are developed for accelerating structures of different function. Essentially new approaches for their adjustment for the set distribution of an accelerating field and frequency (by countering corner change) and some new regulating elements are offered: the end resonant elements of adjustment (EREA) and inductance-capacitor elements (сontrivances). By results of modelling three real accelerating sections which are created at modernization of the multicharge ions linear accelerator were developed. New variants pre-stripping area of the heavy ions accelerator with the relation of mass number to charge A/q = 20 are offered. Надано огляд зустрічно-штирових прискорювальних структур лінійних прискорювачів важких іонів, що розроблялися в ННЦ ХФТІ протягом декількох десятків років. Показано, що в структурах з індивідуальними штангами застосовні всі види фокусувань: квадрупольна, сіткова, змінно-фазова у різних варіантах, високочастотна у різних варіантах та їх комбінації. Для прискорювальних структур різного призначення розроблено відповідні конструктивні рішення. Запропоновано принципово нові підходи для їх настроювання на заданий розподіл прискорювального поля й частоту (шляхом зміни кута зустрічності) і декілька нових регулювальних елементів: кінцеві резонансні елементи настроювання та індуктивно-ємнісні елементи (контрики). За результатами моделювання розроблено три реальні прискорювальні секції, які створювалися при модернізації лінійного прискорювача багатозарядних іонів. Запропоновано нові варіанти передобдиркової ділянки прискорювача важких іонів із відношенням масового числа до зарядового A/q = 20. Представлен обзор встречно-штыревых ускоряющих структур линейных ускорителей тяжелых ионов, разрабатывавшихся в ННЦ ХФТИ на протяжении нескольких десятков лет. Показано, что в структурах с индивидуальными штангами применимы все виды фокусировок: квадрупольная, сеточная, переменно- фазовая в различных вариантах, высокочастотная в различных вариантах и их комбинации. Для ускоряющих структур различного назначения разработаны соответствующие конструктивные решения. Предложены принципиально новые подходы для их настройки на заданное распределение ускоряющего поля и частоту (путем изменения угла встречности) и несколько новых регулирующих элементов: концевые резонансные элементы настройки и индуктивно-емкостные элементы (контрики). По результатам моделирования разработаны три реальные ускоряющие секции, которые создавались при модернизации линейного ускорителя многозарядных ионов. Предложены новые варианты предобдирочного участка ускорителя тяжелых ионов с отношением массового числа к зарядовому A/q = 20.